MicroRNA of N‐region from SARS‐CoV‐2: Potential sensing components for biosensor development. (22nd August 2021) - Halim, Fatin Syakirah; Parmin, N. A.; Hashim, Uda; Gopinath, Subash C.B.; Dahalan, Farrah Aini; Zakaria, Iffah Izzati; Ang, Wei Chern; Jaapar, Nurfareezah Fareezah
Abstract: An oligonucleotide DNA probe has been developed for the application in the DNA electrochemical biosensor for the early diagnosis of coronavirus disease (COVID‐19). Here, the virus microRNA from the N‐gene of severe acute respiratory syndrome‐2 (SARS‐CoV‐2) was used for the first time as a specific target for detecting the virus and became a framework for developing the complementary DNA probe. The sequence analysis of the virus microRNA was carried out using bioinformatics tools including basic local alignment search tools, multiple sequence alignment from CLUSTLW, microRNA database (miRbase), microRNA target database, and gene analysis. Cross‐validation of distinct strains of coronavirus and human microRNA sequences was completed to validate the percentage of identical and consent regions. The percent identity parameter from the bioinformatics tools revealed the virus microRNAs' sequence has a 100% match with the genome of SARS‐CoV‐2 compared with other coronavirus strains, hence improving the selectivity of the complementary DNA probe. The 30 mer with 53.0% GC content of complementary DNA probe 5′ GCC TGA GTT GAG TCA GCA CTG CTC ATG GAT 3′ was designed and could be used as a bioreceptor for the biosensor development in the clinical and environmental diagnosis of COVID‐19. Abstract : An oligonucleotide DNA probe has been developed for the application in the DNA electrochemical biosensor for the early diagnosis of coronavirus disease (COVID‐19). Here, the virus microRNA from the N‐gene of severe acute respiratory syndrome‐2 (SARS‐CoV‐2) was used for the first time as a specific target for detecting the virus and became a framework for developing the complementary DNA probe.